Video analysis of anterior cruciate ligament tears of professional basketball players in the National Basketball Association - Costello, J. P. II; Stauber, Z. M.; Luxenburg, D.; Cohen, J. L.; Tandron, M. C.; Rizzo, M. G. Jr.; Kaplan, L. D. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Anterior cruciate ligament (ACL) tears are devastating for elite athletes, including those in the National Basketball Association (NBA). The purpose of this study was to describe common in-game mechanisms of injury, playing situations, and anatomic positioning of players who sustained an ACL injury in the NBA. METHODS: ACL tears which occurred in NBA games during the previous 16 seasons (2007-2022) and had accessible video clips were identified through publicly available reports. RESULTS: Thirty-one ACL tears were identified with quality videos available. Nearly all players were on offense (93.5%, 29/31). Most ACL tears (29/31, 93.5%) did not involve direct contact to the injured extremity. The most common physical activity at the time of injury was landing from any type of jump (45.2%, 14/31). Anatomically, the knee was frequently in early flexion (58.8%, 10/17) and abducted (77.4%, 24/31); the foot was commonly abducted (87.1%, 27/31); and the hip was usually abducted (64.5%, 20/31) and flexed (80.6%, 25/31). Almost all players had another individual near them at the time of injury, with 90.3% (28/31) and 96.8% (30/31) having someone within 2ft and 5ft. CONCLUSIONS: Most ACL tears occurred inside the lane, regardless of mechanism of injury (26/31, 83.9%). ACL tears in the NBA were primarily not due to direct contact of the injured extremity but did have common anatomic patterns. The findings of this study can be used in the future to help reduce the risk of injury through the adaptation of current training activities.